The Role of Cardiac Computed Tomography Angiography in Risk Stratification for Coronary Artery Disease - Sophie E. van Rosendael, MD, PhD; Arthur Shiyovich, MD; Rhanderson N. Cardoso, MD; Camila Veronica Souza Freire, MD; Alexander R. van Rosendael, MD, PhD; Fay Y. Lin, MD; Gina Larocca, MD; Solomon W. Bienstock, MD; Ron Blankstein, MD; Leslee J. Shaw, PhD (Journal of the Society for Cardiovascular Angiography & Interventions)
Coronary computed tomography angiography (CCTA) allows the assessment of the presence and severity of obstructive and nonobstructive atherosclerotic coronary artery disease. With software developments incorporating artificial intelligence-based automated image analysis along with improved spatial resolution of CT scanners, volumetric measurements of atherosclerotic plaque, detection of high-risk plaque features, and delineation of pericoronary adipose tissue density can now be readily and accurately evaluated for a given at-risk patient. Many of these expanded diagnostic measures have been shown to be prognostically useful for prediction of major adverse cardiac events. The incremental value of plaque quantification over diameter stenosis has yet to be thoroughly discovered in current studies. Furthermore, the physiological significance of lesions can also be assessed with CT-derived fractional flow reserve, myocardial CT perfusion, and more recently shear stress, potentially leading to selective invasive coronary angiography and revascularization. Along with these technological advancements, there has been additional high-quality evidence for CCTA including large randomized clinical trials supporting high-level recommendations from many international clinical practice guidelines. Current trials largely compare a CCTA vs functional testing strategy, yet there is minimal evidence on CCTA plaque-guided therapeutic trials to measure regression of atherosclerosis and prevention of major coronary artery disease events. In this review, we summarize current evidence on comprehensive risk assessment with CCTA and future directions.